2006
DOI: 10.1021/es0518878
|View full text |Cite
|
Sign up to set email alerts
|

Use of Monte Carlo Analysis to Characterize Nitrogen Fluxes in Agroecosystems

Abstract: Intensive agricultural systems are largely responsible for the increase in global reactive nitrogen compounds, which are associated with significant environmental impacts. The nitrogen cycle in agricultural systems is complex and highly variable, which complicates characterization in environmental assessments. Appropriately representing nitrogen inputs into an ecosystem is essential to better understand and predict environmental impacts, such as the extent of seasonally occurring hypoxic zones. Many impacts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…This tool simulates a probable range of outcomes given a set of variable conditions and can be applied within a risk assessment or Life Cycle Inventory framework to capture parameter variability (Huijbregts et al, 2001;Miller et al, 2006;Henriksson et al, 2011). Thus, MC is a technique employed to quantify variability and uncertainty using probability distributions.…”
Section: Monte Carlo Analysismentioning
confidence: 99%
“…This tool simulates a probable range of outcomes given a set of variable conditions and can be applied within a risk assessment or Life Cycle Inventory framework to capture parameter variability (Huijbregts et al, 2001;Miller et al, 2006;Henriksson et al, 2011). Thus, MC is a technique employed to quantify variability and uncertainty using probability distributions.…”
Section: Monte Carlo Analysismentioning
confidence: 99%
“…However, there are significant uncertainties in N 2 O emission calculations (IPCC, 2006), particularly for N 2 O emissions originating in the fraction of N lost via runoff, leaching and volatilization (Reijnders and Huijbregts, 2011). In addition, only a few studies have assessed how this influences the soybean GHG balance (Del Grosso et al, 2009;Smeets et al, 2009;Snyder et al, 2009;Panichelli et al, 2009;Smaling et al, 2008;Reijnders and Huijbregts, 2008;Miller, 2010;Miller et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been shown that parameter uncertainty is inevitable in hydrological modeling and a corresponding assessment should be conducted before model prediction in the decision making process. Studies of parameter uncertainty have been conducted in the area of integrated watershed management (Zacharias et al, 2005), peak flow forecasting (Jorgeson and Julien, 2005), soil loss prediction (Cochrane and Flanagan, 2005), nutrient flux analysis (Murdoch et al, 2005;Miller et al, 2006), assessment of the effect of land use change (Eckhardt et al, 2003;Shen et al, 2010;Xu et al, 2011) and climate change impact assessment (Kingston and Taylor, 2010), among many others. Nevertheless, parameter identification is a complex, non-linear problem and numerous possible solutions might be obtained by optimization algorithms (Nandakumar and Mein, 1997).…”
Section: Z Y Shen Et Al: a Case Study Of Swat Model Applied To Thrmentioning
confidence: 99%